Long-term efficacy, safety, and tolerability of a subcutaneous immunoglobulin 16.5% (cutaquig®) in the treatment of patients with primary immunodeficiencies - Kobayashi, Roger H; Litzman, Jiří; Melamed, Isaac; Mandujano, J Fernando; Kobayashi, Ai Lan; Ritchie, Bruce; Geng, Bob; Atkinson, T Prescott; Rehman, Syed; Höller, Sonja; Turpel-Kantor, Eva; Kreuwel, Huub; et al. (Clinical and experimental immunology, 2022)
A prospective study and its long-term extension examined whether weekly treatment of patients with primary immunodeficiencies (PIDs) with a 16.5% subcutaneous immunoglobulin (SCIg; cutaquig®) confers acceptable efficacy, safety, and tolerability over a follow-up of up to 238 weeks (>4 years). Seventy-five patients received 4462 infusions during up to 70 weeks of follow-up in the main study and 27 patients received 2777 infusions during up to 168 weeks of follow-up in the extension. In the main study, there were no serious bacterial infections (SBIs), and the annual rate of other infections was 3.3 (95% CI 2.4, 4.5). One SBI was recorded in the extension, for an SBI rate of 0.02 (upper 99% CI 0.19). The annual rate of all infections over the duration of the extension study was 2.2 (95% CI 1.2, 3.9). Only 15.0% (1085) of 7239 infusions were associated with infusion site reactions (ISRs), leaving 85.0% (6153) of infusions without reactions. The majority of ISRs were mild and transient. ISR incidence decreased over time, from 36.9% to 16% during the main study and from 9% to 2.3% during the extension. The incidence of related systemic adverse events was 14.7% in the main study and 7.4% in the extension. In conclusion, this prospective, long-term study with cutaquig showed maintained efficacy and low rates of local and systemic adverse reactions in PID patients over up to 238 weeks of follow-up.
Keywords: Immunoglobulin G; syndromy imunologické nedostatečnosti; Bacterial Infections; Humans; intravenózní imunoglobuliny; lidé; bakteriální infekce; Immunoglobulins, Intravenous; prospektivní studie; Immunologic Deficiency Syndromes; Prospective Studies; imunoglobulin G; Treatment Outcome; Infusions, Subcutaneous; výsledek terapie; subkutánní infuze